Impact of early childhood caries on quality of life: Child and parent perspectives - Neerja Singh; Neha Dubey; Monika Rathore; Pallavi Pandey (Elsevier, 2020)
Background: The aim of present study was to examine early childhood caries' impact on oral health-related quality of life from children's self report and parental perception. Methods: 200 healthy children in the age group of 3-5 years and their parents/guardians were enrolled in the study. 100 children diagnosed with early childhood caries (interventional group) and 100 children without caries (control group) along with their parents/guardians participated in face to face interview and responded to Michigan oral health related quality of life scale - child and parent version. Four weeks after full mouth rehabilitation children with ECC and their parents responded to a survey for a follow-up assessment. Data was analyzed and evaluated using Statistical Package for Social Sciences Version 21.0 statistical software and Chi square test. Results: In our study we have found that ECC subjects had poorer oral health-related quality of life compared to caries free subjects. Further one month follow up after complete treatment, the oral health-related QoL improved significantly in ECC children. Conclusions: Early childhood caries has a definite negative impact on the OHRQoL of children. At one month follow up after complete oral rehabilitation, the quality of life improved significanty as assessed by children's self reports as well as parental perceptions of their child's OHRQoL.